Total flavonoids of Abelmoschus manihot ameliorate lipid deposition in HK-2 cells by inhibiting fatty acid uptake mediated by CD36 - Xiaofang Wang; Chenquan Tang; Yi Jiang; Yi Xue; Enchao Zhou (Bangladesh Journal of Pharmacology)
This study aimed to explore the mechanism by which total flavones of Abelmoschl manihot reduce intracellular lipid deposition in HK-2 cells (Human renal cortex proximal tubule epithelial cells) and thus reduce cell apoptosis. Palmitic acid was employed to induce intracellular lipid deposition. The cell proliferation activity was detected by the CCK-8 assay. The cell death status was evaluated by flow cytometry. The intracellular lipid deposition was observed by oil red O and BODIPY probe staining. The expression level of CD36 in HK-2 cells was determined by western blot. The results indicated that total flavones of A. manihot could inhibit the expression of CD36 in HK-2 cells in a dose-dependent manner and reduce lipid deposition. Consequently, total flavones of A. manihot protect HK-2 cells by reducing intracellular lipid deposition by inhibiting CD36-mediated fatty acid uptake.